Extensão e desenvolvimento rural sustentável na Bacia do Paraná 3 - Mattia, Vinícius (2017)
The study of the specificities around the reality of peasant and family farm, and their organizations, make it possible to make inferences about how these social groups are near than the sustainability dimensions. So, the aim of this paper was analyzed some initiatives of extension and sustainable rural development in Parana 3 watershed – BP3. To this, they were elaborated three articles whose the first one analyzed some initiatives in BP3 of services according to precepts of nova Ater to family farm and their organizations, as well as listed demands. The second realized a characterization of six cooperatives of commercialization of family farm products evidencing their way of commercialization and relation with the institutional and conventional markets. In the last one, it was analyzed a specific case of a peasant cooperative using a participative method to evidence the perception of members about strengths and weaknesses of organization. The conclusion showed that the research answered the articles goals purposed and allowed highlight some indicatives as the importance of public polices, services of technical assistance and rural extension and of cooperatives to peasant and family farm.